2006
DOI: 10.21273/hortsci.41.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Uptake and Distribution in a Mature `Pinot noir' Vineyard

Abstract: The nutrient uptake and distribution patterns for N, P, K, Ca, and Mg were determined in mature (23 to 24 year old), field-grown, rainfed grapevines (Vitis vinifera L. `Pinot noir') growing in a red hill soil in Oregon in 2001 and 2002. Biomass, nutrient concentrations, and nutrient contents of all plant organs, including roots, were determined on 14 sampling dates over 2 years. There was no seasonal change in the standing biomass of primary roots (fine feeder roots), small w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
83
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 23 publications
(38 reference statements)
13
83
3
Order By: Relevance
“…This was similar to the findings of a grapevine investigation undertaken in Europe (Wermelinger and Koblet 1990), but contrasts with a North American study conducted in a 23 year old Pinot noir vineyard which found relatively larger amounts of N in the roots and trunk than leaves (Schreiner and Scagel 2006), indicating that older and bigger vines may have the capacity to store more N in root and trunk reserves than measured in the present trial in a 5 year old vineyard.…”
Section: Impact Of Cover Crops On the N-economy Of Vinessupporting
confidence: 86%
See 1 more Smart Citation
“…This was similar to the findings of a grapevine investigation undertaken in Europe (Wermelinger and Koblet 1990), but contrasts with a North American study conducted in a 23 year old Pinot noir vineyard which found relatively larger amounts of N in the roots and trunk than leaves (Schreiner and Scagel 2006), indicating that older and bigger vines may have the capacity to store more N in root and trunk reserves than measured in the present trial in a 5 year old vineyard.…”
Section: Impact Of Cover Crops On the N-economy Of Vinessupporting
confidence: 86%
“…The rate of N uptake by vines increases from bud break and reaches a maximum close to bloom and fruit set during late spring-early summer (Wermelinger and Koblet 1990;Schreiner and Scagel 2006). The soil temperature and water conditions most favorable for rapid mineralization of the N in organic matter are also likely to occur in spring (Mengel 1996;Fillery 2001;Peoples et al 2009).…”
Section: Impact Of Cover Crops On the N-economy Of Vinesmentioning
confidence: 99%
“…This indicates that the vines from solid treatment had lower N-reserves, since the previous year's post-harvest N-uptake, the period of active N buildup in the vine's perennial parts, was in competition with the grass cover crop. A flush of root growth starts at or around bloom, depending on the soil temperature, and active N-uptake by the vines occurs between bloom and veraison and again during post-harvest periods of the current year (Schreiner & Scagel, 2006;Wermelinger & Koblet, 1990;Wermelinger et al, 1991;Yang & Hori, 1979;Zapata, Deleens, Chaillou, & Magne, 2004). In the later stages of berry formation, the N-concentration increased to some extent in cover crop treated berries but continued to be at lower levels compared to clean-cultivated berries.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetative growth of red fescue grass is active from spring to fall and competes with vines for soil nitrogen resources during this time. In addition, N-reserves might continue to contribute up to 50% to the vine growth from bloom to veraison when the reserves are high (Cheng & Xia, 2004;Schreiner & Scagel, 2006). On the other hand, the result of low N-concentration of cover crop berries at harvest could be attributed to the weak sink strength of berries postveraison (Rodrigue-Lovelle and Gaudillere, 2002) along with the reduced N availability in the soils due to the cover crop.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of vine N uptake increases from bud break and reaches a maximum close to bloom and fruit set during late spring-early summer (Schreiner, Scagel, and Baham 2006). From fruit set N is progressively less utilized for vegetative growth and increasingly more utilized by the fruit (Conradie 1986).…”
Section: Introductionmentioning
confidence: 99%